A Comparative Study of Traditional Kashmiri Remedies and Modern Medical Management for Constipation in Srinagar, India - Shellem Mishra; Karina Jawali (Sriwijaya Journal of Internal Medicine, 2023)
Introduction: Constipation is a common gastrointestinal disorder with various causes, significantly impacting quality of life. In Srinagar, India, traditional Kashmiri remedies are frequently employed alongside or as an alternative to modern medical management for constipation. This study aimed to compare the efficacy, safety, and patient satisfaction associated with these two approaches. Methods: A randomized controlled trial was conducted involving 200 adult participants diagnosed with functional constipation in Srinagar. Participants were randomly allocated to either a traditional Kashmiri remedies group (n=100) or a modern medical management group (n=100). The traditional remedies group received individualized herbal formulations and dietary recommendations based on traditional Kashmiri medicine principles. The modern medical management group received standard treatments, including lifestyle advice, fiber supplements, and laxatives. The primary outcome was the change in weekly bowel movement frequency. Secondary outcomes included constipation symptom severity, quality of life, patient satisfaction, and adverse events. Data were collected at baseline, 4 weeks, and 8 weeks. Results: Both groups demonstrated significant improvements in weekly bowel movement frequency, constipation symptom severity, and quality of life. However, no statistically significant difference was observed between the two groups in the primary or secondary outcomes. Patient satisfaction was high in both groups, with a slight preference for traditional remedies due to perceived naturalness and fewer side effects. Conclusion: Both traditional Kashmiri remedies and modern medical management are effective in managing constipation in Srinagar. The choice of treatment should be individualized based on patient preferences, access to care, and cost considerations. Further research is needed to explore the long-term effects and optimal integration of these approaches.